An evaluation of cattle farmers' knowledge of bovine brucellosis in northeast Portugal - J. García Díez; A.C. Coelho (Elsevier, 2013)
Summary: Little information is available regarding the connection between the risk of brucellosis infection in cattle and the lack of training and education of cattle producers. A total of 154 cattle farmers from the Vila Real (northern Portugal) municipality were interviewed in person to evaluate their knowledge of bovine brucellosis.Basic knowledge of the zoonotic characteristics and clinical signs of brucellosis infection and cattle management was obtained from 78.6%, 68.8% and 79.9% of the respondents, respectively. The respondents with infected animals in their herds (odds ratio (OR) 5.5; 95% confidence interval 1.6, 19.5) were more likely to have greater knowledge about bovine brucellosis. The study also revealed a relationship (p < 0.01) between the use of breeding males and farms that were already infected with brucellosis. Moreover, the knowledge that brucellosis is a zoonotic disease was also influenced by the number of farms already infected with brucellosis (p < 0.01).Conversely, the number of respondents who were unaware that bovine brucellosis is a zoonotic disease (25.3%) and a foodborne pathogen (21.4%), and the fact that over half (54.5%) of the respondents believed that bovine brucellosis was a treatable infectious disease was associated with the absence of veterinary assistance on the farm (60.4%).Because the eradication of bovine brucellosis has multiple factors, the success of the national eradication program cannot be based only on the sanitary management of infected herds. Successful eradication will only occur with adequate training programs for farmers, including farm biosecurity, legal fulfillment and veterinary public health programs (in which the role of the veterinarian is fundamental). Keywords: Brucellosis, Cattle, Biosecurity, Education, Farmers